2014
DOI: 10.1519/jsc.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 8-Week Plyometric Training on Leg Power, Jump and Sprint Performance in Female Soccer Players

Abstract: The aim of this study was to determine the effect of 8-week plyometric training (PT) on the leg power and jump and sprint performance in female soccer players. Eighteen female soccer players from Women Second League (age = 18.2 ± 2.3 years, height = 161.3 ± 5.4 cm, body mass = 56.6 ± 7.2 kg) were randomly assigned to control (n = 9) and plyometric (n = 9) groups. Both groups continued together with regular technical and tactical soccer training for 4 days a week. Additionally, the plyometric group underwent PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 20 publications
7
43
1
11
Order By: Relevance
“…Although the differences in the type of training programme applied make comparisons between different studies difficult, others have also found an increase in sprint performance after plyometric training in male (Brito et al, 2014) and female (Ozbar, Ates, & Agopyan, 2014) soccer players; however, this was the first study to compare the effects of in-season short-term plyometric training on 30 m sprint times in both male and female soccer players. Because vertical strength and maximal-intensity exercise are related with sprint performance (Loturco et al, 2015), the maximal-intensity vertical jump drills completed during intervention might have positively affected sprint performance in the plyometric training groups.…”
Section: Discussionmentioning
confidence: 89%
“…Although the differences in the type of training programme applied make comparisons between different studies difficult, others have also found an increase in sprint performance after plyometric training in male (Brito et al, 2014) and female (Ozbar, Ates, & Agopyan, 2014) soccer players; however, this was the first study to compare the effects of in-season short-term plyometric training on 30 m sprint times in both male and female soccer players. Because vertical strength and maximal-intensity exercise are related with sprint performance (Loturco et al, 2015), the maximal-intensity vertical jump drills completed during intervention might have positively affected sprint performance in the plyometric training groups.…”
Section: Discussionmentioning
confidence: 89%
“…Jumping performance was assessed in 24 of the included studies . Within‐group improvements in jumping performance were ranging from 3.4% to 26.3% in the PLY groups vs −6% to 8% in the control groups, following 4‐12 weeks of intervention (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Corluka, Bjelica, Vasiljevic, Bubanja, Georgiev i Zeljko (2018) ukazuju na način koji omogućuje optimizaciju parametara morfoloških svojstava i sastav tijela. Pored toga, pliometrijski trening može biti koristan za poboljšanje sprinterskih i skakačkih sposobnosti fudbalerki, što se posebno odnosi na takmičarski period sezone tokom kojeg nema puno raspoloživog vremena za dodatne treninge (Ozbar, Ates & Agopyan, 2014).…”
Section: Differences In the Level Of Anthropological Characteristics unclassified